Recent Development of Quinoxaline Based Polymers/Small Molecules for Organic Photovoltaics. Issue 21 (14th July 2017) - Gedefaw, Desta; Prosa, Mario; Bolognesi, Margherita; Seri, Mirko; Andersson, Mats R.
Abstract: Among the various molecular designs developed for the synthesis of conjugated polymers and small molecules for optoelectronic applications, the donor: acceptor (D–A) approach is the most widely explored method over the past decades. Through the covalent linkage of electron‐rich and electron‐deficient units, a plethora of medium‐low band gap materials has been developed and tested in organic photovoltaic devices. In particular, the quinoxaline aromatic structure and its derivatives are among the most studied electron deficient aromatic units used in D–A structures. Quinoxaline based materials are endowed with characteristics that are useful for large scale production in real world applications, such as easy synthetic procedures and excellent stability in air. Moreover, the use of quinoxaline based polymers/small molecules in bulk heterojunction (BHJ) devices led to power conversion efficiencies over 9%. Considering the potential of quinoxaline based materials, this review gathers together quinoxaline based polymers and small molecules reported in the literature during the last 5 years, summarizing and discussing the structure‐properties relationships for this class of organic semiconductors, aiming to serve as a background and to promote efforts for the further development of new quinoxaline derivatives with improved and advanced properties for future applications. Abstract : This review summarizes the recent developments of quinoxaline‐based polymers and small molecules for photovoltaic applications . The structure‐properties relationships for this class of organic semiconductors are discussed by correlating the results reported in the literature in the last five years. The attractive properties and the compatibility with the massive production requirements anticipate a bright future for quinoxaline‐based semiconductors in photovoltaics.